A systematic approach to the improvement of new product design- a case study on durable goods industry - Akdağ, Levent (My University, 2004)
A SYSTEMATIC APPROACH TO THE IMPROVEMENT OF NEW PRODUCT DESIGN- A CASE STUDY ON DURABLE GOODS INDUSTRY In this dissertation a new approach was developed for improving new product design process. A modular, customizable and updateable systematic approach, SNPDA (Systematic New Product Design Approach), supported with numerical computation, was developed to model the iterative characteristic of the design process. Application of the approach on a case study in the durable goods industry was performed. Results and discussions regarding the applicability of the approach were presented with conclusions and recommendations for further studies. In the first part of the dissertation, the methodologies and tools used within the study were stated. Quality Function Deployment (QFD) and Axiomatic Design (AD) methodologies were used to capture and to map the Voice of the Customer in to the design process. Technical Requirements and Part Characteristics (by QFD) or Functional Requirements and Design Parameters (by AD) were obtained and used to form the Design Matrix (DM). Design Structure Matrix (DSM) method was used to obtain the relationships between the design parameters. The dependency between the part characteristics was represented by the Part Design Structure Matrix (P-DSM). A specific and unique mapping method was developed to transfer this information to tasks level of the design process. Task Design Structure Matrix (T-DSM) was used to represent the dependencies between the activities of the whole design process. Numerical codes were developed in FORTRAN programming language to compute, to evaluate and to improve the task sequencing and execution alternatives. Cost and benefit analysis of these alternatives was performed. The developed approach was able to model sequential (serial), concurrent (parallel) and hybrid (mixed) task execution strategies. A heuristic-type of optimization technique was presented to obtain the sub-optimal task sequencing with an acceptable computation requirement. Validation of the numerical approach was provided by tests cases. To further clarify the understanding of the approach, a case study was conducted on durable goods industry. The design development cost and design development time values were followed as the design performance parameters. The results of the case study showed the change in the performance parameters for various task sequencing and executions strategies. Therefore, the model allowed the determination of better alternatives. June 2004Levent Akdağ

YENİ ÜRÜN TASARIMINI İYİLEŞTİRMEDE BİR SİSTEMATİK YAKLAŞIM -DAYANIKLI TÜKETİM ENDÜSTRİSİNDE ÖRNEK BİR UYGULAMA Bu doktora tezinde, yeni ürün tasarım prosesinin geliştirilmesi için yeni bir yaklaşım geliştirilmiştir. Tasarim prosesinin iteratif karakteristiğini modelleyebilmek için, sayısal hesaplama ile desteklenmiş modüler; özelleştirilebilir ve geliştirilebilir bir sistematik yaklaşım - SNPDA (Systematic New Product Design Approach)- geliştirilmiştir. Yaklaşımın uygulaması, dayanıklı tüketim endüstrisindeki bir örnek uyuglama üzerinde yapılmıştır. Yaklaşımın uygulanabilirliği gözönüne alınarak, sonuçlar ve öneriler raporlanmıştır. Bu doktora tezinin ilk kısmında, çalışmada kullanılan metodolojiler ve araçlar ifade edilmiştir. Müşterinin Sesi'nin elde edilmesi ve tasarım prosesinde kullanılabilmesi için, Kalite Fonksiyon Açınımı (QFD) ve Axiomatik Tasarım (AD) metodolojileri kullanılmıştır. Tasarım Matrisi'nin oluşturulmasında, QFD metodundan elde edilen Teknik Gereksinimler ve Parça Karaktestikleri veya AD metodundan elde edilen Fonksiyonel Gereksinimler ve Tasarım Parametreleri kullanılmıştır. Tasarım Yapısal Matrisi (DSM) yöntemi kullanılarak tasarım parametreleri arasındaki ilişki belirlenmiştir. Parça karakteristikleri arasındaki bağımlılığın belirlenmesi için Parça-Tasarım Yapısal Matrisi (P-DSM) yöntemi kullanılmıştır. Bu bilgilerin, tasarım prosesindeki görev seviyelerine transferi özgün ve benzeri olmayan bir eşleştirme yöntemi kullanılarak sağlanmıştır. Tasarım prosesindeki tüm aktivitelerin aralarındaki ilişkileri temsil etmek için ise, Görev-Tasarım Yapısal Matrisi (T-DSM) metodu kullanılmıştır. Görev sıralamaları ve gerçekleştirmeleri alternatiflerinin hesaplanması, değerlendirilmesi ve geliştirilmesi için, FORTRAN programlama dilinde programlar geliştirilmiştir. Bu alternatifler için, maliyet ve kar analizleri yapılmıştır. Geliştirilen metod, sıralı (seri), eşzamanlı (paralel) veya hibrit (karma) görev gerçekleştirme stratejilerini modelleyebilmektedir. Kabul edilebilir bir hesaplama ihtiyacı duyacak şekilde optimum-yakın görev sıralamalarına ulaşmak amacıyla, bir bulgusal tip optimizasyon tekniği sunulmuştur Sayısal yaklaşımın doğrulanması test uygulamalarıyla sağlanmıştır. Yaklaşımın anlaşılabilirliğini daha da artırmak için, dayanıklı tüketim endüstrisine ait bir örnek yürütülmüştür. Tasarım performans parametreleri olarak, tasarım geliştirme maliyeti ve tasarım geliştirme zamanı kullanılmıştır. Örnek uygulama sonuçları, farklı görev sıralamaları ve gerçekleştirme stratejileri için performans parametrelerinin değiştiğini göstermiştir. Bu nedenle, model daha iyi alternatiflerin belirlenmesine izin vermiştir. Haziran 2004Levent Akdağ
Keywords: Ürün Tasarımı